2015
DOI: 10.14227/dt220115p17
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Dissolution Profiles of Seven Metformin Formulations in Simulated Intestinal Fluid

Abstract: Dissolution testing is used to evaluate the performance of pharmaceutical products. This study compared the dissolution profiles of seven immediate-release metformin 500-mg formulations, including two products with the trade name Glucophage, in simulated intestinal fluid (SIF) at pH 6.8 buffer without enzymes. Other characteristics investigated were absolute weight and drug content. These formulations were marketed in Trinidad and Tobago and are categorized as Class 3 drugs by the Biopharmaceutics Classificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 8 publications
(6 reference statements)
1
30
0
1
Order By: Relevance
“…In case of R1 and R2, our results that show dissolution dissimilarity is in consistence with Stuart et al [31] who assumed that the two MH innovator products having similar trade name (Glucophage), but came from different manufacturers, were statistically different regarding their dissolution profiles. Likewise, Crison et al [44] stated that MH IR tablets obtained from different markets showed diverse drug release profiles.…”
Section: Usp Apparatus IVsupporting
confidence: 88%
See 2 more Smart Citations
“…In case of R1 and R2, our results that show dissolution dissimilarity is in consistence with Stuart et al [31] who assumed that the two MH innovator products having similar trade name (Glucophage), but came from different manufacturers, were statistically different regarding their dissolution profiles. Likewise, Crison et al [44] stated that MH IR tablets obtained from different markets showed diverse drug release profiles.…”
Section: Usp Apparatus IVsupporting
confidence: 88%
“…This variability in MH release may be due to differences in particle size and/or surface area of MH particles, uneven distribution of hydrodynamic force [50] or differences in the method of manufacturing, compression force or machinery [52]. [31,53] stated that the difference in dissolution profiles of products could be attributed to the excipients and/or the manufacturing process. Furthermore, Berthelsen et al [54] reported that excipients might disturb the drug-filter interaction/adsorption in USP apparatus IV, causing differences in dissolution profiles and interfering with the prediction of in vivo data.…”
Section: Comparative In Vitro Release Study Of Mh Cr Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the dissolution profile curve was prepared by plotting percentage release of drug versus time of sample withdrawal. As per USP, the tablets were considered to comply with the standards if at least 80% of the drug released in 30 min (14,24). The difference factor (f 1 ) and similarity factor (f 2 ) for all generic products were determined with reference to the innovator product.…”
Section: Dissolution Testmentioning
confidence: 99%
“…The similarity factor was calculated only if either the reference or test products released less than 85% of the active ingredient within 15 min with n = 12 (12).…”
Section: Statistical Analysesmentioning
confidence: 99%